A Novel Mutation in SLC26A4 Causes Nonsyndromic Autosomal Recessive Hearing Impairment. Issue 2 (February 2017) - Wolf, Axel; Frohne, Alexandra; Allen, Matthew; Parzefall, Thomas; Koenighofer, Martin; Schreiner, Markus M.; Schoefer, Christian; Frei, Klemens; Lucas, Trevor
Abstract : Background: Heterozygous mutations in GJB2 (MIM: 121011) encoding the gap junction protein connexin 26 are overrepresented in patient groups suffering from nonsyndromic sensorineural hearing impairment (HI) implying the involvement of additional genetic factors. Mutations in SLC26A4 (MIM: 605646), encoding the protein pendrin can cause both Pendred syndrome and autosomal recessive, nonsyndromic HI locus 4 type sensorineural HI (MIM: 600791). Objectives: Aim of this study was to investigate the role of SLC26A4 coding mutations in a nonsyndromic hearing impairment (NSHI) patient group bearing heterozygous GJB2 35delG mutations. Design: We analyzed the 20 coding exons of SLC26A4 in a group of patients (n = 15) bearing heterozygous 35delG mutations and exclusively suffering from congenital HI. Results: In a case of bilateral congenital hearing loss we identified a rare, novel SLC26A4 exon 2 splice donor mutation (c.164+1delG) predicted to truncate pendrin in the first cytoplasmic domain, as a compound heterozygote with the pathogenic missense mutation c.1061T>C (p.354F>S; rs111033243). Conclusions: Screening for SLC26A4 mutations may identify the genetic causes of hearing loss in patients bearing heterozygous mutations in GJB2 . Hypothesis: SLC26A4 coding mutations are genetic causes for nonsyndromic HI in patients bearing heterozygous GJB2 35delG mutations.